Sociodemographic and Perinatal Predictors of Early Pregnancy Per- and Polyfluoroalkyl Substance (PFAS) Concentrations - Sagiv, Sharon K; Rifas-Shiman, Sheryl L; Webster, Thomas F; Mora, Ana Maria; Harris, Maria H; Calafat, Antonia M; Ye, Xiaoyun; Gillman, Matthew W; Oken, Emily (Environmental science & technology, 2015)
Per- and polyfluoroalkyl substances (PFASs), used in food packaging and stain-resistant coatings, are suspected developmental toxicants that are ubiquitous and persistent in the environment. We measured plasma PFAS concentrations during early pregnancy (median = 9.7 weeks gestation) among 1645 women in the Boston-area Project Viva cohort, recruited during 1999-2002. We used multivariable linear regression to estimate associations of sociodemographic and perinatal predictors, including measures of pregnancy physiology (albumin, glomerular filtration rate (GFR)), with log-transformed plasma PFAS concentrations. Geometric mean concentrations for the four main PFASs, perfluorooctanesulfonate (PFOS), perfluorooctanoate (PFOA), perfluorohexanesulfonate (PFHxS) and perfluorononanoate (PFNA) were 25.4, 5.7, 2.5, and 0.6 ng/mL, respectively, comparable with general U.S. population concentrations during those years. Higher early pregnancy PFAS concentrations were associated with younger age (except PFNA), less educational attainment, nulliparity, no history of breastfeeding and higher prepregnancy body mass index in adjusted models. In addition, lower GFR was associated with 3-4% higher PFAS concentrations and higher albumin was associated with 4-6% higher PFAS concentrations. Our results show associations consistent (parity and breastfeeding) and less consistent (age and education) with previous studies. We also report associations with GFR and albumin, which were strongly related to PFAS concentrations and thus could confound estimates of PFAS-outcome associations in epidemiologic studies.